PERKEMBANGAN BAHASA ANAK BERDASARKAN TEORI JEAN PIAGET PADA SISWA KELAS 1 MI MUSLIMAT NU DEMAK - Laili Zumala; Indah Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Children's language development is a fundamental aspect of elementary education because it plays a crucial role in developing communication, thinking, and social interaction skills. Language is not only a means of communication but also a reflection of children's cognitive development. This study aims to describe the language development of first-grade students at MI Muslimat NU Demak based on Jean Piaget's cognitive development theory. The study used a qualitative approach with descriptive methods. Data were collected through classroom learning observations, in-depth interviews with class teachers, and documentation of student learning outcomes. The results showed that first-grade students' language development is still at the pre-operational stage moving towards concrete operational, characterized by the ability to construct simple sentences, the use of language that is still egocentric, limited abstract vocabulary, and reliance on concrete experiences. These findings are in line with Piaget's theory which states that language development is closely related to children's cognitive structure. The role of teachers and the learning environment has been shown to have a significant influence in stimulating language development through social interaction and contextual learning